STRATEGI MENINGKATKAN MINAT BACA MURID DISMP MUHAMMADIYAH 1 LUMAJANG - Ramadhan, Sony; Sujinah; M. Sulthon Amien; Rizkika Zakka Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading is one of several language skills that students must master to facilitate their understanding and acquisition of new knowledge. Reading is typically practiced based on strong interest. The Ministry of Education and Culture initiated a drive to strengthen literacy culture in schools through the School Literacy Movement (GLS) program. The scope of the school literacy movement or GLS includes the physical school environment, facilities and infrastructure, support from all school elements, including teachers and students, and various programs aimed at increasing students' interest in reading within the educational environment. The focus of this research is as follows: first, the reading interest of eighth-grade students at Muhammadiyah 1 Lumajang Junior High School during the academic year. Second, the factors that encourage and hinder the reading interest of eighth-grade students at Muhammadiyah 1 Lumajang Junior High School. Third, to identify strategies to increase reading interest in eighth-grade students at Muhammadiyah 1 Lumajang Junior High School. This research is descriptive. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results indicate that the reading interest of eighth-grade students at Muhammadiyah 1 Junior High School Lumajang in the 2025/2026 academic year is moderate. This is indicated by the tendency to read only when there is schoolwork or teacher instructions. Students visit the library only when there is a lesson that requires textbooks and teacher instructions. Factors that encourage student reading interest include an enjoyment of novels, the active role of the principal and teachers in literacy development, mentoring in reading and writing programs, a diverse book collection, and parental support for reading habits. Factors that hinder student reading interest include laziness, the dominant use of devices for social media and online games, and an uncomfortable library. Strategies to increase student reading interest include: Creating a friendly and conducive school environment; Providing appreciation, both praise and awards, for students who read diligently and produce written works; Schools strive for a literate academic environment by allocating 10-15 minutes for reading together programs; and providing mentoring and guidance to students who read diligently and produce written works in book form.